Hubungan Ekspresi Matriks Metaloproteinase-9 dengan Jenis Histopatologi Karsinoma Serviks dan Invasi Limfovaskular - Meta Oktora; Salmiah Agus; Pelsi Sulaini (Perhimpunan Dokter Spesialis Patologi Anatomik Indonesia (PDSPA), 2019)
BackgroundMatrix Metalloproteinase 9 (MMP-9) is a proteolytic enzyme assumed to have an important role in cervicalcarcinogenesis. Limfovascular invasion (LVI) and higher expression of MMP-9 will make cervical tissuedegradation faster, invasion process and metastasist easier. Adenocarcinoma is suspected of having poorprognostic than squamous cell carcinoma (SCC). The aim of this study was to examine the relationshipbetween expression of MMP-9 with histopathological cervical carcinoma and LVI.MethodsA cross sectional analytic study was performed on 36 sample that divided into 18 KSS and 18 adenokarsinoma.Samples were tooken from block paraffin from surgery or biopsy in Anatomic Pathology laboratories are locatedin West Sumatra. Sample are reviewed and found the LVI. Immunohistochemical was staining with primaryantibody MMP-9 then its expression were assessed in stroma and cytoplasmic cell tumour.ResultsMMP-9 expression was found positive in 80.6% (41.1% for SCC and 58.6% for cervical adenocarcinoma. Themean of expression of SCC was 17.4 and cervical adenocarsinoma was 19.56. Expression of MMP-9 waspositive in LVI sample.ConclusionThere is not significant relationship between the expression of MMP-9 with type of histopatologic cervicalcarcinoma (p=0.088) and LVI (p=0.566). Expression of MMP-9 in cervical adenocarcinoma was higher thanSCC, but it was not significant (p=0.563).